THE ANTIMICROBIAL ACTIVITY OF MIMOSA PUDICA L. - Gangai Abirami, S. K.; Sudha Mani, K.; Nisha Devi, M.; Nirmala Devi, P. (International Journal of Ayurveda and Pharma Research, 2015)
Mimosa pudica L. (Mimosaceae) is the herb that shows sensation on touch and its grows as weed in almost all parts of the country. It majorly possesses an antibacterial, antifungal, antioxidant, antiinflammatory, antiasthmatic, analgesic and antidepressant activities. In the present study, antimicrobial activity of Mimosa pudica was tested with various extracts such as petroleum ether, ethylacetate, acetone and aqueous against various human pathogenic bacteria such as Escherichia coli, Pseudomonasaeurogiosa, Lactobacillus, Salmonellatyphi and Staphylococcus aureus also with plant pathogenic fungus such as Pestalotiafoedians, Fusariumoxysporum and Paecilomycesvariotii at different concentrations. Out of the selected various solvent extracts, in bacterial study, acetone extract showed a maximum zone of inhibition against Staphylococcus aureus. In fungal study, ethyl acetate extract showed maximum zone of inhibition against Fusariumoxysporum.